Predictors of severity and mortality in children hospitalized with respiratory syncytial virus infection in a tropical region (2014)
Respiratory syncytial virus (RSV) is one of the leading causes of acute lower respiratory infection (ALRI) in infants and young children. Although ALRI is a major public health problem in developing countries located in tropical areas, studies about RSV epidemiology in these regions are scarce. In a retrospective cohort study, we investigated the epidemiology and predictive variables that reflect disease severity and mortality in young children hospitalized with ALRI due to RSV in Colombia, South-America, during a 2-year period (2009–2011). Of a total of 6,344 children with a diagnosis of ALRI, we selected 2,147 (33.8%) that were positive for RSV. After controlling for pre-existing conditions, we found that independent predictors of severe disease in our population included age <6 months (RR 2.01; CI 95% 1.70–2.38; P < 0.001), prematurity (RR 1.61; CI 95% 1.20–2.17; P = 0.001), congenital heart disease (RR 2.03; CI 95% 1.16–3.54; P = 0.013), and mixed RSV-adenovirus infection (RR 2.09; CI 95% 1.60–2.73; P < 0.001). Multivariate analysis identified that cancer (RR 31.60; CI 95% 5.97–167.13; P < 0.001) is a predictor of mortality in our RSV-infected pediatric population independently of age and other co-morbidities. RSV is an important cause of ALRI in infants and young children living in tropical regions, especially during the rainy season. The identified predictors of severe disease and mortality should be taken into account when planning interventions to reduce the burden of ALRI in young children living in these regions.